Digital Transformation: A Qualitative Study on the Impact of Artificial Intelligence (AI)-Based Learning Media on Accounting Learning Motivation of Gen Z Students in Vocational High Schools - Fitriantinah Fitriantinah (CV. Publikasi Indonesia, 2026)
Generation Z students, as digital natives, possess unique learning characteristics that are heavily reliant on technology. However, accounting is often perceived as a rigid and monotonous subject in vocational education. The integration of Artificial Intelligence (AI) into learning media offers a new level of personalization and interactivity that has the potential to reshape student motivation. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews and classroom observations. The data analysis followed the Miles and Huberman model, facilitated by ATLAS.ti software to ensure systematic coding and network analysis. The results indicate that AI-based tools enhance students' intrinsic motivation by providing instant feedback and reducing academic anxiety. AI acts as a